Cancer‐specific promoters for expression‐targeted gene therapy: ran, brms1 and mcm5. (5th July 2016) - Chen, Xuguang; Scapa, Jacqueline E.; Liu, David X.; Godbey, W T.
Abstract: Background: To expand the library of promoters that can be used for expression‐targeted gene delivery to cancer cells, the specificity and strength of expression of three cancer‐related gene promoters was evaluated: RAS‐related nuclear protein ( P ran ), breast cancer metastasis suppressor 1 ( P brms1 ) and minichromosome maintenance complex component 5 ( P mcm5 ). Methods: The expression of reporter genes under the control of these promoters demonstrated selectivity in cancer cell lines of breast, prostate and ovarian origins versus a panel of normal cell types. The P ran was next used to regulate the expression of a bioactive exon (a constitutively active form of human caspase 3) to induce apoptosis in cancer cells. Further evaluation was performed in an orthotopic model of murine bladder cancer. Results: The average strengths of reporter expression had relative intensities of 99.8% ( P ran ), 87.7% ( P brms1 ) and 55.8% ( P mcm5 ) versus the strong P cmv ‐driven positive control. Comparisons of expression‐targeted reporter gene expression for these three promoters versus the clinically interesting promoter for the human telomerase reverse transcriptase gene ( P hTERT ) yielded an improvement of two‐ to 15‐fold. Following transfection, cell death was evident from morphologic observations and viability assays performed on the cancer cells lines, with little (if any) effects seen when the same genes were delivered to normal cells. Cell viability was reduced by up to 60% after one treatment, with cell death via apoptosis implied by caspase 3 detection. During the in vivo preclinical study, reduced tumor burden, lack of mineralization and decreased inflammation were demonstrated after only three treatments. Conclusions: The ran, brms1, and mcm5 promoters have the specificity and strength needed for cancer‐specific expression‐targeted gene therapy. p ran in particular produced exciting results when coupled with a version of the caspase 3 exon to treat bladder cancer. Copyright © 2016 John Wiley & Sons, Ltd.